Reactions of Some Spiro Chromenes with Bromine and Chlorine - Abdullah Alsehaibani, Hamad (Asian Journal of Chemistry, 2010)
The addition of halogens and hydrolysis of some 2,2´-spiro-2-cycloalkyl chromenes have been investigated and the effects of the size of the spiro-annelated on the chemistry of spiro chromenes are described.